Perencanaan Mesin Pembuat Baglog Media Jamur Tiram - Wiyono, Teguh; Siswanto, Siswanto; Utami, Desi Tri (Politeknosains, 2023)
The empowerment of small and household industries is a government policy based on the people's economy. This is a form of trust in the independence of the community in carrying out its economic activities. In fact, small and household industries are industries that are resilient to uncertain economic conditions like today. The oyster mushroom media baglog production business group is among the oyster mushroom baglog craftsmen in Trayu Village, Banyudono District, Boyolali Regency. This business group makes oyster mushroom baglogs manually by hand directly, patiently and diligently one by one baglogs are produced, Over time, the baglog production business group was unable to serve the demand for baglogs for planting mushrooms, so they started to open up insights to cooperate with any party who could provide solutions in making baglog filling machines electrically. So that the work in making baglogs can increase and can meet the demand of consumers and customers who make oyster mushrooms and can compete with other home industries, by applying a more practical machine and a larger capacity so that it is reliable, in increasing the production of oyster mushroom media baglogs, economically able to increase the income of its workers. The implementation of this oyster mushroom growing media baglog making machine engineering program specifically improves skills that support productivity and can increase the income of the oyster mushroom media baglog production business group and it is hoped that this program on a national scale will increase regional per capita income.